Decentralising REDD+: Lessons Learned from REDD+ Himalaya Project of Nepal (Journal of Forest and Livelihood, 2018)
How REDD+ (Reducing Emissions from Deforestation and Forest Degradation) can be institutionalised in already decentralised forestry governance remains a critical question across the developing countries. Lessons of pilot projects carried out at local or sub-national level have been crucial to draw insights into REDD+ decentralization. Taking Nepal’s REDD+ Himalaya Project as a case study, this paper illustrates how REDD+ can be institutionalised at sub-national level by stimulating the existing enablers and addressing associated issues hand in hand. While doing so, the study adopted number of approaches, including document reviews; key informant interview and small group meetings with the stakeholders of the project at national and sub-national level. We found that the project has contributed to decentralising Nepal’s REDD+ process, albeit at a token scale, through adopting number of approaches, including but not limited to, capacitating sub-national level REDD+ institutions and REDD+ actors and encouraging interactive decision-making process. In addition, recognition and redress of livelihood and social problem is other key intervention that acted as an accelerator. The project, however, faced some institutional, programmatic and practical issues which need to be resolved for better REDD+ results in the days to come.